Quercetin-mediated SIRT1 activation attenuates collagen-induced mice arthritis. (28th October 2021) - Shen, Pan; Lin, Weiji; Ba, Xin; Huang, Yao; Chen, Zhe; Han, Liang; Qin, Kai; Huang, Ying; Tu, Shenghao
Abstract: Ethnopharmacological relevance: Herba taxilli (HT, Sangjisheng in Chinese), which is composed of the dried stems and leaves of Taxillus chinensis (DC.) Danser, has been commonly used to treat inflammation and arthritis in traditional Chinese medicine (TCM). Quercetin (Que) is a major active flavonoid component isolated from HT and is one of the quality control indexes of HT. In the clinical practice of TCM, formulas containing HT are commonly used to treat rheumatoid arthritis (RA). Recent studies have shown that Que exerts antiarthritic effects. However, the mechanism by which Que treatment affects RA is not fully understood. Aim of the study: This study aimed to explore the antiarthritic activity of Que in a collagen-induced arthritis (CIA) mouse model and investigate the underlying mechanisms. Materials and methods: The antiarthritic activity of Que was evaluated in a CIA mouse model by determining the paw clinical arthritis scores and left ankle thicknesses and by conducting micro-PET imaging and histopathological analysis of ankle joint tissues. The proinflammatory cytokine (IL-6, TNF-α, IL-1β, IL-8, IL-13, IL-17) levels in the serum and ankle joint tissues were measured by ELISA. Mitochondrial oxidative stress was assessed by biochemical methods. Mitochondrial biogenesis was analysed by RT-qPCR. The protein levels of silent information regulator 1 (SIRT1), peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), nuclear respiratory factor 1 (NRF1), mitochondrial transcription factor A (TFAM), high-mobility group box 1 (HMGB1), Toll-like receptor 4 (TLR4), p38, phospho-p38, extracellular signal-regulated kinases (ERK)-1/2, phospho-ERK1/2, p65, and phospho-p65 in ankle joint tissues were detected by Western blot analysis. A total of 30 RA patients were recruited to investigate the relationship between the disease activity score (DAS28) and the SIRT1, PGC-1α, NRF1, and HMGB1 plasma levels. Results: Que treatment decreased the clinical score and left ankle thickness of CIA mice, attenuated the synovial inflammation and hyperplasia and bone/cartilage destruction in ankle joints, and decreased the secretion of IL-6, TNF-α, IL-1β, IL-8, IL-13, and IL-17. Mechanistically, Que treatment improved impaired mitochondrial biogenesis and mitochondrial function by regulating the SIRT1/PGC-1α/NRF1/TFAM pathway and inhibited inflammation via the HMGB1/TLR4/p38/ERK1/2/NF-κB p65 pathway. Notably, epidemiological data revealed correlations between abnormal circulating levels of SIRT1, PGC-1α, NRF1, HMGB1 and RA disease activity in patients. Conclusions: Our data suggested a potential role of Que as a dietary therapeutic drug for RA treatment that may act through SIRT1 to target mitochondrial biogenesis. Additionally, the role of impaired mitochondrial biogenesis in RA was evaluated. Graphical abstract: Image 1